Prevalence of Joint Hypermobility and Patterns of Articular Manifestations in Patients with Inflammatory Bowel Disease - P. Vounotrypidis; E. Efremidou; P. Zezos; M. Pitiakoudis; E. Maltezos; N. Lyratzopoulos; G. Kouklakis (Gastroenterology Research and Practice)
Objective. The objective is the investigation of Joint Hypermobility (JH) and the Hypermobility Syndrome (HMS) in patients with inflammatory bowel disease (IBD). Methods. We examined 83 patients with IBD and 67 healthy individuals for the presence of JH. Patients were excluded if they were under 18 or over 50 years of age and if they had other conditions which affect joint mobility. The x2 and the Fisher exact test were used appropriately between study groups. Odds ratios (ORs) for the risk of JH and HMS in IBD groups were calculated. Results. A total of 150 individuals (83 IBD patients and 67 healthy controls) participated in the study. 69 IBD patients, 41 with Crohn's Disease (CD) and 28 with ulcerative colitis (UC), were finally eligible. JH was detected in 29 CD patients (70.7%), in 10 UC patients (35.7%), and in 17 healthy control subjects (25.4%). Significant difference was detected on JH in CD patients as compared to UC patients (𝑃=.0063) and controls (𝑃<.0001). The estimated OR for JH was 7.108 (95% CI: 2.98–16.95) in CD and 1.634 (95% CI: 0.63–4.22) in UC patients. HMS was detected in 5 (12.2%) CD and in 1 (3.57%) UC patients. The OR for HMS in CD was 3.75 (95% CI: 0.41–34.007), while 7 (17.1%) CD patients had overlapping symptoms for both HMS and early spondylarthropathy. Conclusions. JH and the HMS are common in CD patients, thus articular manifestations should be carefully interpreted. This implies an involvement of collagen varieties in the pathogenesis of IBD.